2011
DOI: 10.1007/s10802-011-9553-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Positive and Negative Parenting Behavior with Childhood ADHD: Interactions with Offspring Monoamine Oxidase A (MAO-A) Genotype

Abstract: Relatively little is known about the potential interplay between genetic and environmental influences on attention-deficit/hyperactivity disorder (ADHD), including gene-environment interaction (G×E). There is evidence that parenting behavior interacts with offspring genotype in the development of externalizing problems, but studies have largely focused on explicit maltreatment rather than differentiated measures of parenting behavior, including positive and negative parenting. We tested the interactive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…Fourth, we observed lower internal consistency estimates in the Alabama Parenting Questionnaire factors, which is relatively consistent with previous studies demonstrating lower estimates particularly for corporal punishment and inconsistent discipline (Dadds, Maujean, & Fraser, 2003; Ellis & Nigg, 2009; Shelton et al, 1996). However, previous studies from this sample, using the same APQ parenting factors, have demonstrated their predictive validity with relevant criteria, including offspring inattention, ODD, and CD symptoms, aggression, and rule-breaking behavior (Falk & Lee, 2012; Li & Lee, 2012; Tung & Lee, 2014; Tung, Li, & Lee, 2012). Fifth, because adult ADHD and offspring ADHD were measured using adult self-report versus parent structured interview, respectively, parent and offspring ADHD may not necessarily reflect the same underlying construct.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Fourth, we observed lower internal consistency estimates in the Alabama Parenting Questionnaire factors, which is relatively consistent with previous studies demonstrating lower estimates particularly for corporal punishment and inconsistent discipline (Dadds, Maujean, & Fraser, 2003; Ellis & Nigg, 2009; Shelton et al, 1996). However, previous studies from this sample, using the same APQ parenting factors, have demonstrated their predictive validity with relevant criteria, including offspring inattention, ODD, and CD symptoms, aggression, and rule-breaking behavior (Falk & Lee, 2012; Li & Lee, 2012; Tung & Lee, 2014; Tung, Li, & Lee, 2012). Fifth, because adult ADHD and offspring ADHD were measured using adult self-report versus parent structured interview, respectively, parent and offspring ADHD may not necessarily reflect the same underlying construct.…”
Section: Discussionmentioning
confidence: 80%
“…Parent ADHD symptoms were also positively associated with inconsistent discipline and nonsupportive responses to offspring negative emotions (Mokrova, O’Brien, Calkins, & Keane, 2010). Although the association between parenting behavior and offspring ADHD reflects reciprocal and transactional processes (Burke, Pardini, & Loeber, 2008; Psychogiou, Daley, Thompson, & Sonuga-Barke, 2007), frequent negative parenting and low positive parenting exacerbate ADHD (Li & Lee, 2012; Sonuga-Barke & Halperin, 2010) and independently predict the development of comorbid oppositional defiant disorder (ODD) and conduct disorder (CD; Chronis et al, 2007; Ellis & Nigg, 2009). In a cross-sectional study of 181 children with and without ADHD, maternal inconsistent discipline uniquely predicted offspring ADHD, controlling for parent ADHD as well as child ODD and CD (Ellis & Nigg, 2009).…”
Section: Parenting Behavior As a Mediatormentioning
confidence: 99%
“…The current study used data from four samples of children with and without ADHD (Chronis-Tuscano et al, 2008; Li & Lee, 2012a; Mikami, Jack, Emeh, & Stephens, 2010), yielding a full sample of 526 children. Teacher data were available for 385 of the total sample.…”
Section: Methodsmentioning
confidence: 99%
“…They were recruited using mailings and presentations to local physicians, ADHD self-help groups, schools, and mental health professionals. Expanded details about each sample’s recruitment, ascertainment, and participant characteristics are explained elsewhere (Chronis-Tuscano et al, 2008; Li & Lee, 2012a; Mikami, Jack, Emeh, & Stephens, 2010). The pooled sample was 71% male, 6 to 12 years of age ( M = 7.4; SD = 1.1), and ethnically diverse: 48.4% Caucasian, 22.1% African American, 6.0% Latino, 13.9% mixed-race, and 9.6% “other.”…”
Section: Methodsmentioning
confidence: 99%
“…Martel et al (2011) previously reported G×E effects involving a variant in the promoter region of DRD4 and inconsistent parenting in predicting inattentive ADHD symptoms. Similarly, Li and Lee (2012) documented interactions between the high-activity variant of the monoamine oxidase-A gene (MAO-A), a gene involved in dopamine degradation, and negative (but not positive) parenting dimensions in predicting ADHD inattentive symptoms among boys. Recent work has also extended G×E models to predict additional outcomes, with findings indicating that other psychosocial factors, including potential enriching environments (e.g., positive peer affiliation) may interact with DRD4 variants to predict putamen volume (Richards et al 2016).…”
Section: Discussionmentioning
confidence: 99%